Exploring the Pedagogical Impact of Visual Wall Charts on Student Engagement and Understanding in Arabic Language Learning: A Qualitative Insight - Nur Laila Azizah; Luthfiyah Khoirun Nisa; Naifah (https://unikhams.ac.id/, 2025)
Background: Many Indonesian students still find Arabic learning difficult to follow, often showing limited motivation and comprehension. Introducing visual materials such as wall charts provides a more tangible and appealing way to present linguistic concepts in class. Aims: The present study explores how wall charts can be used as an instructional medium to strengthen learners’ engagement and understanding in Arabic classrooms. It focuses on examining their educational value in creating meaningful participation and sustained motivation among students. Methods: This research adopted a qualitative case study carried out at MA NU 03 Sunan Katong. The data were collected from tenth-grade learners and an Arabic language instructor through class observations, interviews, and documentation. The analysis followed the interactive model of Miles and Huberman and involved triangulation to ensure the credibility and depth of interpretation. Result: The use of wall charts was found to increase students’ enthusiasm, attention, and ability to recall Arabic structures and vocabulary. Learners responded positively to the visual layout, which encouraged collaboration and dialogue during lessons. Teachers also noted improved classroom flow and reduced monotony. Although the printed materials are static, the approach successfully built a stimulating environment where students could learn through both observation and interaction. Conclusion: The study confirms that visual wall charts can serve as an effective pedagogical bridge between traditional and active learning in Arabic language education. Their visual form encourages deeper comprehension, interactive communication, and creativity, making them highly suitable for contemporary learner-centered teaching models.